The potential of Tithonia diversifolia green manure for improving soil quality for cauliflower (Brassica oleracea var. Brotrytis L.) - Hafifah, H; Sudiarso, S; Maghfoer, M D; Prasetya, B (Brawijaya University, 2016)
This study aimed to analyze the effect of Tithonia diversifolia green manure and cow manure on soil quality and yield of cauliflower. A field experiment was conducted in the village of Tegalgondo, Karangploso District of Malang Regency. Eight treatments tested were control (no added manures), T.diversifolia 8.15 t/ha, cow manure 25.85 t/ha, NPK fertilizer 1.35 t/ha, T.diversifolia 4.08 t/ha + cow manure 12.93 t/ha, T.diversifolia 4.08 t/ha + NPK fertilizer 676 kg/ha, cow manure 12.93 t/ha + NPK 676 kg/ha and T.diversifolia 2.69 t/ha + cow manure 8.53 t/ha + NPK fertilizer 446 kg/ha. Soil quality was monitored at top soil (0-20 cm) at planting time and 30 days after planting. Soil samples were collected and analyzed for chemical and physical properties. Yield of cauliflower was observed at the time of harvest or 44 days after planting. The results showed that application of green manure could significantly change the physical and chemical properties of the soil. The decrease of bulk density of about 27.47%, increase of organic carbon of about 12.60%, increase of total N of about 53.87%, increase of available P of about 64.24 mg/kg, and exchangeable K of about 8.34 cmol/kg were observed in T. diversifolia treatment. The increase of pH of about 1.75%, and total porosity of about 17.73% was found in cow manure treatments. The increased water holding capacity of about 10.70% was found in T. diversifolia + cow manure treatments and increased stability aggregate about 23.54% was found in T. diversifolia + cow manure + NPK treatments. There was a significant increase of fresh weight of flower about 666.67 g/plant in T. diversifolia + NPK treatment.